Quantifying the Effects of Climate Change on Aircraft Take-Off Performance at European Airports - Jonny Williams; Paul D. Williams; Federica Guerrini; Marco Venturini (Aerospace)
This work uses state-of-the-art climate model data at 30 European airport locations to examine how climate change may affect summer take-off distance required—TODR—and maximum take-off mass—MTOM—for a 30-year period centred on 2050 compared to a historical baseline (1985–2014). The data presented here are for the Airbus A320; however, the methodology is generic and few changes are required in order to apply this methodology to a wide range of different fixed-wing aircraft. The climate models used are taken from the 6th Coupled Model Intercomparison Project (CMIP6) and span a range of climate sensitivity values; that is, the amount of warming they exhibit for a given increase in atmospheric greenhouse gas concentrations. Using a Newtonian force-balance model, we show that 30-year average values of TODR may increase by around 50–100 m, albeit with significant day-to-day variability. The changing probability distributions are quantified using kernel density estimation and an illustration is provided showing how changes to future daily maximum temperature extremes may affect the distributions of TODR going forward. Furthermore, it is projected that the 99th percentile of the historical distributions of TODR may by exceeded up to half the time in the summer months for some airports. Some of the sites studied have runways that are shorter than the distance required for a fully laden take-off, which means they must reduce their payloads as temperatures and air pressures change. We find that, relative to historical mean values, take-off payloads may need to be reduced by the equivalent of approximately 10 passengers per flight, as these significant increases (as high as approximately 60%) show a probability of exceeding historical extreme values.